A STUDY OF PSYCHO-SOCIO-DEMOGRAPHIC VARIABLES OF SUICIDE ATTEMPTERS IN HILLY AREAS OF UTTARAKHAND - Upadhyaya, S K; Gupta, Sudhir; Sharma, A; Joshi, A (Indian Journal of Community Health, 2012)
Abstract Suicide is a complex, yet preventable public health problem resulting from multiple factors. The number of suicides in the country during the decade (1999–2009) has recorded an alarming increase of 15% (NCRB). Data of suicide attempters show predominance of females, unemployed, singles and those suffering from major medical or psychiatric illness. Present study was carried out to assess various factors in suicide attempters in subhimalayan zone of Uttarakhand. Objectives: 1) To assess the role of psycho-socio-demographic variables including past history, precipitating factors and mode of attempt. 2) To make the psychiatric diagnosis of suicide attempters. Study Design: Cross sectional study. Setting: Teaching hospital of VCSG Government Medical Science and Research Institute, Srinager garhwal, Uttarakhand. Participants: 50 cases of suicidal attempters who attended the teaching hospital. Sample size was kept 50 as frequency of suicide attempters reaching to this hospital is not very high because this is in a hilly area with sparse population. Study duration : May 2011 to Nov 2011 Results : Total 50 cases of suicidal attempters were inquired. Suicidal attempts were found maximum (60%) in the group 21 to 40 years in both males and females. House wives and unemployed men were most prone to suicides. Females from joint families attempted suicide significantly more than from nuclear families. History of depression in females and history of substance abuse in family members were important predictors for suicidal attempt. Family quarrels and marital disharmony were most common factors and poisoning was mostly common method for suicidal attempts in both sexes.